Peter rabbit goes to the island level 1 - Veness, Coleen Degnan (London : Ladybird books ., 2016)
Old Brown has Peter Rabbit's book. Peter, Benjamin and Lily want it back! This brand-new Ladybird Readers ELT range is an essential teaching tool to create, encourage and support young learners of English as a foreign language. Each reader is very carefully written to meet strict syllabus criteria but the text is rich and striking artwork makes each book appealing to children. Launching with twenty-eight readers, ranging from classic fairy tales and non-fiction to favourite children's brands and original stories.
Keywords: English - Book; Ladybird English books